Identification of hepatic fibroblast growth factor 21 as a mediator in 17β‐estradiol‐induced white adipose tissue browning. Issue 10 (2nd May 2018) - Hua, Lun; Zhuo, Yong; Jiang, Dandan; Li, Jing; Huang, Xiaohua; Zhu, Yingguo; Li, Zhen; Yan, Lijun; Jin, Chao; Jiang, Xuemei; Che, Lianqiang; Fang, Zhengfeng; et al.
ABSTRACT: Both ovarian E2 and hepatic fibroblast growth factor 21 (FGF21) are critical for energy homeostasis and white adipose tissue browning. Estrogen receptor α (ERα) is abundantly expressed in liver. However, whether FGF21 has a role in E2‐induced white adipose tissue browning remains uncertain. In this study, we showed that hepatic Fgf21 expression and secretion during estrus cycle changed with the tetradian oscillatory secretion of circulation E2 in adult, female mice, with their peak expressions and secretions at the proestrus. In addition, exogenous E2 robustly stimulated liver Fgf21 expression and elevated serum FGF21 concentrations, which induced browning gene expression and reduced the tissue weight in subcutaneous white adipose in mice with ovariectomies. The inhibitor of mammalian target of rapamycin (mTOR) and of ERα blocked the induction effect of E2 on the expression of Fgf21 in primary hepatocytes, which revealed that E2 might stimulate FGF21 expression via the ERα‐mTOR pathway. Furthermore, FGF21 liver‐specific deficiency abolished E2‐induced white adipose browning in mice with ovariectomies. This study indicates that ovarian E2 increased liver FGF21 expression directly, which in turn, functioned as an endocrine signal to influence inguinal white adipose tissue browning.—Hua, L., Zhuo, Y., Jiang, D., Li, J., Huang, X., Zhu, Y., Li, Z., Yan, L., Jin, C., Jiang, X., Che, L., Fang, Z., Lin, Y., Xu, S., Li, J., Feng, B., Wu, D. Identification of hepatic fibroblast growth factor 21 as a mediator in 17β‐estradiol‐induced white adipose tissue browning. FASEB J. 32, 5602–5611 (2018). www.fasebj.org